INVESTMENT PLANNING IN ISLAMIC WEALTH MANAGEMENT: A SYARIAH PERSPECTIVE ON GROWTH AND SUSTAINABILITY - M.Hakim Sitompul; Sugianto; Marliyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Islamic wealth management has emerged as a critical area for addressing ethical and sustainable investment needs, driven by the principles of Shariah compliance. This study aims to explore the integration of Islamic wealth management tools with a focus on investment planning, growth, and sustainability. It addresses gaps in regulatory frameworks, Shariah governance, and the adoption of fintech and blockchain technologies. Using a bibliometric and thematic analysis approach, this research reviews data collected from Scopus and Web of Science, analyzing trends and debates in the field of Islamic finance over the last two decades. The study reveals significant advancements in instruments like Sukuk, green Sukuk, and Islamic mutual funds, alongside challenges in ensuring Shariah compliance and integrating sustainability frameworks. Findings highlight the potential of Islamic financial tools to support sustainable economic growth and financial inclusion, provided that governance structures and technological adoption are improved. The implications underscore the need for stronger collaboration between academia and industry to address global financial and socio-economic challenges. This study contributes to the literature by offering comprehensive insights into the role of Islamic finance in achieving sustainable development goals while bridging theoretical and practical gaps.